Co-creation, Creative Expression, and Artificial Intelligence for the Inclusion of Individuals with Intellectual Disabilities - Centurión, Nureen; Rogoski, Valeria; Roa, Rafael; Guedes, Leandro Soares (Anais da Conferência Latino-Americana de Interação Humano-Computador (CLIHC); 2026: Anais da XII Conferência Latino-Americana de Interação Humano-Computador, 2026)
This paper investigates the integration of creative computing and accessible technologies to support the digital inclusion of individuals with intellectual disabilities. We conducted participatory workshops combining visual programming (Scratch), tangible interaction (Makey Makey), and multimodal content generated with Artificial Intelligence. Fifteen participants interacted with educational games designed to connect abstract concepts with concrete physical actions. Data were collected through structured observation and analyzed using exploratory thematic analysis. Results indicate patterns of increased engagement, social interaction, and progressive autonomy, particularly in activities combining tangible interaction and multimodal feedback. The study also highlights the role of iterative co-creation, human mediation, and AI-assisted content adaptation in supporting participation across diverse cognitive profiles.